Сучасне управління проектами розробки програмного забезпечення на основі технологій штучного інтелекту - Акімов, М. О. (ХНУРЕ, 2023)
According to a study by the analytical platform Cognilytica, 86% of project managers approve of AI technologies. And in companies where AI has already been implemented, productivity on projects has improved by 20%. In the future, the term “project team” will mean a collection of people and AI assistants. Artificial intelligence will make it possible to automate work in the administrative field, remove the human factor from decisions, and effectively use a data-driven approach. This article focuses on the application of AI technology in modern software project management from three aspects including application background, application value, and application suggestions, to promote the awareness of project managers about artificial intelligence